The Relationship of Peer Social Support with Student Learning Motivation - Fira Stevani Sulva; Dina Sukma (Universitas Negeri Padang, 2020)
This research is motivated by the phenomenon in the field still found students who have low motivation to following the learning process. One of the factors causing motivation to learn is the environmental conditions of students who do not support so students do not have an interest in learning and social relationships of students with their peers This study aims to see an overview of students' learning motivation, peer social support, and test the relationship of social support peers with student learning motivation. This research is a descriptive correlational study. With a sample of 222 students selected using a sampling technique chosen by simple random sampling technique. Data collection uses peer support social questionnaires and learning motivation with Likert scale models. The results of this study indicate: (1) peer social support is in the high category with a score of 118 and a percentage of 53.2%, (2) learning motivation is in the high category with a score of 129 and a percentage of 58.1%, (3) there is a relationship a significant positive between peer social support with learning motivation with rxy = 0.458 and a significant level of 0,000. The findings of this study can be a reference for BK teachers in making programs to provide BK services to students.